La Odisea como antecedente literario de Alfanhuí, de Rafael Sánchez Ferlosio - Sanz Morales, Manuel (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
This article suggests that some literary motives, most of them fantastic in nature, that may be found in the novel Industrias y andanzas de Alfanhuí (1951), by Rafael Sánchez Ferlosio (a writer born in 1927, who won the Cervantes Prize in 2004), were derived from, and inspired by, similar fantastic elements in Homer’s Odyssey. The above mentioned motives are analysed, and some external facts are adduced, in order to support the suggested hypothesis. Said external facts show that Ferlosio was deeply interested in the literature of Greece and Rome, and in Homer and the Odyssey in particular
Keywords: Classical Tradition; Homer; Odyssey; R; Sánchez Ferlosio; Alfanhuí